MAKNA NIAT BISNIS PENGUSAHA MUSLIM BISNIS KULINER DI KABUPATEN KUTAI TIMUR - Sismanto Sismanto; Sri Andriani; Syafi’atul Mir’ah Ma’shum; Yusnia Binti Khalifah (At-Tawazun, Jurnal Ekonomi Syariah, 2026)
The culinary sector is one of the fastest-growing economic sectors and has become an important component of community economic activity, including in East Kutai Regency. In practice, Muslim entrepreneurs do not perceive business merely as an economic activity but also as an expression of spiritual values, social responsibility, and worship. This study aims to explore the experiences of Muslim entrepreneurs in managing culinary businesses, analyze the meaning of entrepreneurial intention, and describe the patterns of social action among Muslim entrepreneurs engaged in culinary business activities in East Kutai Regency. This study employed a qualitative approach based on Alfred Schutz’s social phenomenology. Data were collected through in-depth interviews, observations, and documentation involving Muslim culinary entrepreneurs who were selected through purposive sampling. The data were analyzed using data condensation, data display, and conclusion drawing through a thematic approach based on the concepts of because motive and in-order-to motive. The findings indicate that life and spiritual experiences, family background, and future business orientation shape the meaning of entrepreneurial intention among Muslim entrepreneurs. They perceive business as a form of worship, a means of fulfilling family responsibilities, a way to seek divine blessings, and a means of contributing to society. Their patterns of social action are reflected in business management based on Islamic values, family-oriented workplace relationships, customer-oriented service, and business practices that emphasize honesty and trustworthiness. This study contributes to the development of Islamic business phenomenology by providing a deeper understanding of the subjective meanings of entrepreneurial intention and social action among Muslim entrepreneurs engaged in culinary business activities.